NEBIVOLOL: A THIRD GENERATION BETA BLOCKER AS ANTIHYPERTENSION AGENT - Wirantari, Ni Putu; Jawi, I Made; Satriyasa, Bagus Komang (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Hypertension is a silent killer because it causes complications in vital organs unwitting patients. Beta blockers are generally a choice of safe and effective drugs for initial treatment of hypertension. However, the current hypertension treatment guidelines said beta blockers were not suitable use as first-line therapy because of complications caused. On the use of atenolol found an increased incidence of cardiovascular death of 24%, 14% and cardiac complications 23% cerebrovascular complications. Nebivolol is a third-generation beta-blocker that is highly selective for ?1-adrenergic receptors and has the ability as a direct vasodilator was able to stimulate the activity of endothelial L-arginin/nitric oxide synthase, is expected nebivolol can reduce blood pressure so can achieve blood pressure that expected.
Keywords: nebivolol, beta blocker, hypertension